POLA-POLA KOMUNITAS SITUS GUA KAWASAN TIMUR JAWA - Nurani, Indah Asikin (BRIN, 2001)
Research on caves in Java, especially East Java, has been carried out by several foreign researchers such as van Es, van Stein Callenfels, Willems, and H.R. van Heekeren in Ponorogo, Situbondo, Pacitan, Jember, Tuban, and Bojonegoro Regencies. The research is more of an exploratory nature to explore cave settlements in Java. Meanwhile, with a thematic focus on spatial studies, the Balai Arkeologi Yogyakarta has conducted research on groups of caves in Jember Regency (Mount Watang), Bojonegoro Regency (Dander) and in Ponorogo Regency (Sampung). Meanwhile, similar research has also been carried out by the Puslit Arkenas in the cave group in Gunungkidul to Pacitan (Gunung Sewu).